From Early Starters to Late Finishers? A Longitudinal Study of Early Foreign Language Learning in School. Issue 3 (5th May 2017) - Jaekel, Nils; Schurig, Michael; Florian, Merle; Ritter, Markus
Abstract : Foreign language education has now been implemented at the elementary school level across Europe, and early foreign language education has gained traction following language policies set by the European Commission. The long‐term effects of an early start, however, have not received ample scientific scrutiny. The present study assessed early receptive skills of two cohorts of English language learners in Year 5 (beginning of secondary education in Germany) and two years later in Year 7. The factors distinguishing between these two cohorts were onset of foreign language education and the amount of language exposure. The effects of the earlier start were found in the results for Year 5, when the early cohort outperformed peers with less and later exposure to English. However, in Year 7, the late starters surpassed their early starting peers.